Revealed Competition for Greenfield Investments between European Regions - Martijn J. Burger; Bert van der Knaap; Ronald S. Wall (Tinbergen Institute, 2012)
In the modern economy, cities are assumed to be in fierce competition over attracting foreign investments in leading sectors of the world economy. Despite the rich theoretical discourse on these 'wars', it remains unclear which territories are competing with each other over which types of investments Combining insights from international economics, international business, and urban systems literature, we develop an indicator to measure revealed competition between territories for investments based on the overlap of investment portfolios of regions. Taking competition for greenfield investments between European regions as a test subject, we identify competitive market segments, derive the competitive threat a region faces from other regions, the competitive threat regions pose to other regions, and the most important market segments in which regions compete. We show that European regions with similar locational endowments pose a fiercer competitive thre at to one another. In addition, regions that are sufficiently large and distinctive, face the smallest average competitive threat from all other regions.
urn:NBN:nl:ui:15-1765/34708
Keywords: R12; F21; H70; 330; territorial competition; greenfield investments; Europe; Auslandsinvestition; Standortwettbewerb; Produktionsstandort; Europa